Determinants and outcomes firm state of innovativeness in Malaysian service sector : a study on knowledge-intensive business services firm - Md Noh, Ab. Majid (2017)
Many Malaysian firms, particularly firms in the service sector are reported to be lagging behind the manufacturing in terms of productivity growth and outputs, which imply the lack of innovativeness. This research explores the key determinants of firm innovativeness affecting the performance of the knowledge-intensive business services (KIBS). These firms serve as an agent for innovation and the lack of innovative performance among firms in Malaysia in a way can be attributed to KIBS innovativeness. Applying the resource-based view, knowledge-based view and knowledge-based theory of inter-firm collaboration, a cross-sectional sample survey field study on 200 KIBS firms was undertaken to investigate four determinants of firm's innovativeness namely its culture, firm's design, entrepreneurial behaviors and network collaboration strategies; and this study further examined how firm's innovativeness affects their business performance. A partial-least square structural equation modeling (PLS-SEM) software (i.e. SmartPLS Ver. 2.0.M3) was applied for data analysis. The results showed that all hypothesized structural relationships are well substantiated and all determinants of firm's innovativeness are consistent across two major KIBS typologies. Entrepreneurial behavior among professional staffs is found to be the key determinant for KIBS innovativeness. Innovative capabilities and client integration are found to partially mediate firm 's innovativeness and performance relationship. Contrary to the previous belief, a relatively higher proportion of university graduates in KIBS would not increase firm's innovativeness. Firm's size, age, and external information are also found not affecting the firm's innovativeness. The results further demonstrated that adhocracy culture as one of the four dimensions of firm's culture hence conveys the greatest role in shaping an innovative culture in KIBS. Corporate entrepreneurship and innovative behavior (or intrapreneurship) equally governs entrepreneurial behavior in KIBS. Functional integration among inter-departmental staff helps to facilitate firm's design (structure) that promotes innovativeness. Network collaboration is found to be chiefly shaped by KIBS collaborative strategy with commercial labs or private research and development institutions. The general resource-based and the knowledge-based theory of inter-firm collaboration are fully supported in this study. However the specific knowledge-based theory of firm employed to substantiate the role of knowledge as the underpinning theory of firm innovativeness failed to provide full support. Methodological implications are discussed and several improvements for future research are recommended.